Peripheral nervous system assessment in acromegaly patients under somatostatin analogue therapy - YAVUZ, DİLEK; ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (SPRINGER, 2017)
Purpose Acromegaly is known to affect peripheral nervous system (PNS) causing carpal tunnel syndrome (CTS) and polyneuropathy. The frequency of these disorders and the evaluation methods vary among studies. In the present study, we aimed to examine PNS of acromegaly patients under somatostatin analogue (SSA) therapy. Methods Forty-eight acromegaly patients (26 F/22 M, 45.58 +/- 11.6 years) under SSA treatment and 44 healthy controls (25 F/19 M, 47.46 +/- 8.7 years) were assessed by symptom questionnaires, neurologic examination and electrophysiological studies. Results 87.5 % of the acromegaly patients had at least one abnormal finding regarding PNS. With the incorporation of palm-wrist median nerve conduction velocity method, we detected CTS in 50 % of patients. Polyneuropathy was less frequent (29.2 %). Both conditions were independent from the coexisting diabetes mellitus (p = 0.22 for CTS, p = 0.71 for polyneuropathy). Polyneuropathy but not CTS was more common among biochemically uncontrolled acromegaly patients rather than those under control (p = 0.03; p = 0.68, respectively). Conculsion Our findings emphasize the high prevalence of peripheral nervous system involvement in acromegaly patients under SSA therapy and importance of neurological evaluation of these patients. Early diagnosis and treatment of the disease may reduce the PNS involvement.
Keywords: Acromegaly; Peripheral nervous system; Carpal tunnel syndrome; Polyneuropathy; CARPAL-TUNNEL-SYNDROME; MANAGEMENT; NEUROPATHY; CONDUCTION; ULTRASOUND; PAIN